A partnership approach to the design and use of a quantitative measure: Co-producing and piloting the WASH gender equality measure in Cambodia and Nepal. Issue 1 (31st December 2022) - Gonzalez, Diana; Abdel Sattar, Rana; Budhathoki, Ratan; Carrard, Naomi; Chase, Rachel P.; Crawford, Joanne; Halcrow, Gabrielle; Kozole, Tyler; MacArthur, Jess; Nicoletti, Christopher; Toeur, Veasna; Basnet, Min Prasad; et al.
ABSTRACT: The connections between WASH and gender equality have been extensively explored and documented using qualitative approaches, but not yet through quantitative means in ways that can strengthen WASH programming. The Water, Sanitation and Hygiene Gender Equality Measure (WASH-GEM) is a novel quantitative multidimensional tool co-produced in partnership between researchers and practitioners. This article explores three dimensions of the WASH-GEM co-production and implementation: (i) the role of partnerships in co-production processes for bringing contextual and practitioner knowledge into measure development; (ii) selected results from the validation pilot in Cambodia and Nepal ( n = 3, 056) that demonstrate ways in which the measure can inform WASH programming through analysis at different levels and with different co-variants; and (iii) the collaborative process of translating research into programming. The study illustrates that strong partnership and co-production processes were foundational for the development of a conceptually rigorous quantitative measure that has practical relevance. The findings presented in this article have implications for future measure development and WASH programming that aims to influence gender equality in rural communities.